The degree of practicing educational accountability among school principals in Al-'Aqeeq Governorate, Saudi Arabia; from the point of view of teachers and teachers - Al-Ghamdi, Saad Misfir Safar Al-Hilli; Al-Shatnawi, Nawaf Musa (Journal of Educational and Psychological Sciences, 2018)
The study aimed at revealing the degree of application of principals and principals of public education schools in Al-Aqiq Governorate in Al-Baha region in Saudi Arabia to educational accountability from the point of view of teachers working with them. The questionnaire was used as a tool for study. It was distributed to a random sample of 277 individuals, of whom 155 were males and 122 were females. Statistical data processing using the SPSS system: The results of the study showed that the degree of application of school principals to the educational accountability of the tool as a whole came at an average of (4,26), with a very high estimate. In the field of functional discipline, the average was (4,31). In the field of work and achievement it was average (4.2) The field of professional ethics among school principals was average (4,26), all of them were very large. The results showed no statistically significant differences between the average responses of the study sample in the fields of the study instrument according to gender variables and years of experience. There were statistically significant differences according to the variable of the educational stage in the fields of professional ethics, work and achievement, as well as in the tool as a whole for the benefit of the workers in the primary stage.
Keywords: educational accountability; school principals; Al-Aqiq Governorate